From gamer personality, via motivation, to game choice: Typifying gamers and games based on survey data. Issue 2 (1st September 2019) - Kolo, Castulus; Lüst, Niklas
Today's economic success of video games is paralleled by a debate on presumed correlations of certain game play with problematic motivations and personalities, respectively. To shed light on a potential relation between personality, motivations and game choice we conducted an online survey (n = 1612). It confirms the applicability of the five-factor OCEAN model of personality in a German-speaking gaming context. Here, Yee's gamer motivation model as a longer-term psychological concept, contrasting rather short-term motives and incentives, is replicated. Motivations are derived from a principal component analysis of over 40 items and found to form clusters that correlate with specific personalities. Additionally, with 'motivational footprints' and related 'gamer personalities' certain games are favoured. The results suggest that games should be seen as identity management tools rather than means to assume alternative personas. Knowing the particularly enticing combinations of motivations met, may guide the development of future games for selected personalities.